Tid for anerkjennelse Andre verdenskrig i nåtid og i fortid - Bjerkås, Trond; Hagen, Thomas V. H.; Aaby, Gunhild (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
2020 saw the 80th anniversary of the occupation of Norway on 9 April 1940 and the 75th anniversary of Norway's liberation on 8 May 1945. The anniversaries provided an opportunity to reflect on these central events in Norwegian history, and to take a closer look at the war for the sake of collective remembrance. This was the background for the 2020 Agder Seminar. This anthology consists of eight chapters that illuminate in different ways the relationship between memory and repression in the history of our understanding of the Second World War. The chapters are wide-ranging, from theory-based analyses of recognition as a concept and a phenomenon, to empirical studies of various groups' struggle for recognition. The contributors represent a number of different disciplines within the social sciences.